South African conglomerates: A qualitative analysis - R. G.J. Mackintosh; F. E. Bisotto (South African Journal of Business Management, 1981)
This qualitative analysis is based on research on conglomerates not previously undertaken in South Africa. Founded on the work of corporate strategy and development theorists, the research is aimed at establishing a 'character profile' of South African conglomerates. What differentiates passive and acquisitive conglomerates in terms of organizational structure, management function, style, and strategy, is also considered. The information for this analysis is derived from the results of a mail survey. The research findings indicate that in general South African conglomerates are structured on a multi-divisional basis with divisions specializing in product-market rather than functional relationships. Divisions tend to be controlled at arm's length by their corporate head offices, who perform auxiliary and co-ordinating functions. Compared to acquisitives, passives appear to be less flexible in their management style, function, and control. In terms of their strategy, passives tend to be, for the immediate future at least, more aggressive than acquisitives. Hierdie kwalitatiewe ontleding is gebaseer op navorsing oor konglomerate wat nie voorheen in Suid-Afrika onderneem is nie. Die navorsing, gebaseer op die werk van teoretici oor ondernemingstrategie en -ontwikkeling, beoog om 'n 'karakterprofiel' van Suid·Afrikaanse konglomerate daar te stel. Die verskilpunt tussen passiewe en aankopende ('acquisitive') konglomerate wat organisasiestruktuur, bestuursfunksie, styl en strategie betref, word ook beskou. Die inligting vir hierdie ontleding is verkry uit die resultate van 'n opname wat per pos geloods is. Die navorsingsbevindinge dui aan dat Suid-Afrikaanse konglomerate in die algemeen gestruktureer is op 'n multi-afdelingsbasis, met afdelings wat meer spesialiseer volgens produkmark as volgens funksionele verwantskappe. Afdelings word dikwels op 'n afstand beheer deur die moedermaatskappy se hoofkantoor, wat ondersteunende en koordinerende funksies verrig. In vergelyking met aankopende maatskappye, is passiewe maatskappye skynbaar minder buigsaam in hulle bestuurstyl, funksionering en beheer. Wat hulle strategie betref, neig passiewe konglomerate om ten minste ten opsigte van die onmiddellike toekoms, meer aggressief as aankopende konglomerate te wees.